Caregiver Burden and Family Quality of Life in Early Intervention: The Role of Mothers and Family Confidence - Pau García-Grau; Gabriel Martínez-Rico; Rómulo J. González-García; Claudia Tatiana Escorcia-Mora; Margarita Cañadas-Pérez (MDPI AG, 2024)
(1) Background: Because life events when there is a family member with a disability can affect the overall family wellbeing, contributing to enhance family quality of life (FQoL) in the field of early childhood intervention has become a priority. However, it is a distal outcome that needs other short-term outcomes to be addressed, some of them under the potential impact of support services. This study examines the relationships between caregiver burden, family confidence, and FQoL, as well as the influence of child and family variables. (2) Method: A total of 58 families with children in early intervention from four Spanish communities participated. Hierarchical regression was conducted to assess the relevance of each predictor. Also, a mediation was performed to investigate the mediating role of family confidence. (3) Results: The family income impacted FQoL scores, and when burden and confidence were added, it was no longer relevant. Mothers with higher levels of confidence predicted a higher FQoL. Finally, we found a complete mediation of family confidence in the relations between severity and caregiver burden on FQoL. (4) Conclusions: Caregiver burden and family confidence affect FQoL. Building families' confidence contributes to attenuating the impact of burden on FQoL.